2019
DOI: 10.1177/1750698019863152
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory of war veterans: A mixed-studies systematic review

Abstract: This paper reviewed articles on autobiographical memories of veterans who fought several major battles around the world. A total of 28 articles, reporting 11 quantitative, 16 qualitative, and 1 mixed-methods study, were identified through a search conducted in 11 major databases. Convergent thematic analysis of the findings extracted five recurrent themes: (1) memory features, (2) memory content, (3) self and memory, (4) culture and memory, and (5) theoretical accounts. Veterans’ memories were mostly aligned w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Hence, we can assert that the years 1969–1973 are a transition period through which the Bangladeshi people attained a new national identity. Preferential recollection of memories from this period is due to the availability of numerous self-relevant memories that became integrated with the participants’ personal narratives (Islam et al, 2021 ). The period also coincided with the timing of identity formation as most of our participants (81.72%) were in their adolescence and early adulthood during 1969–1973, thus intensifying their memory recollection (Conway et al, 2005 ; Rubin & Schulkind, 1997 ; Rubin et al, 1986 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we can assert that the years 1969–1973 are a transition period through which the Bangladeshi people attained a new national identity. Preferential recollection of memories from this period is due to the availability of numerous self-relevant memories that became integrated with the participants’ personal narratives (Islam et al, 2021 ). The period also coincided with the timing of identity formation as most of our participants (81.72%) were in their adolescence and early adulthood during 1969–1973, thus intensifying their memory recollection (Conway et al, 2005 ; Rubin & Schulkind, 1997 ; Rubin et al, 1986 ).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that two different factors have been operating during veterans’ memory recall - one related to encoding and another to retrieval. First, veterans encoded war memories better than nonveterans because those memories were personally significant and defined who they are (Conway & Pleydell-Pearce, 2000 ; Islam et al, 2021 ). Second, veterans' increased use of H-DAPs is perhaps due to their current veteran identity – a factor that operates at the retrieval level.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, self-defining memories are characterized by affective intensity and repetitiveness in recalling (they serve as "reference points to provide guidance or reinforcement with respect to specific current situations in the )), as well as associativeness (they are associated with a network of related memories that share similar goals, concerns, outcomes, and affective responses 11 ); mental time travels to self-defining memories are also especially vivid Singer & Salovey, 1993). Years of study have demonstrated that self-defining memories have a significant role in individuals' life goals and emotional experiences (see, e.g., Islam et al, 2019;Singer et al, 2013;Singer & Bonalume, 2010;Sutin & Robins, 2005;Sutin & Stockdale, 2010;Wood & Conway, 2006). For example, Singer and Blagov (2004) argue that self-defining memories may serve as the lens through which individuals perceive new experiences, and as such they can create self-fulfilling patterns of interactions that further reinforce narrative scripts 12 they previously delivered; thus, self-defining memories can schematize repetitive actionoutcome-emotional response sequences (Singer & Bonalume, 2010).…”
Section: Psychology Of Memorymentioning
confidence: 99%
“…Research has shown that people who have had traumatic experiences, for example, a history of abuse, face more difficulty in remembering specific autobiographical memories than participants who do not have such experiences (25). Several studies have established that OGM contributes to the development and maintenance of emotional disorders among trauma survivors (18), such as veterans (23,26) and people with histories of abuse (27). In other words, emotional disorders may lead a person's memories toward bias in selecting negative and frightening events (28).…”
Section: Autobiographical Memory Impairment and Mental Health Outcomesmentioning
confidence: 99%